2018
DOI: 10.5858/arpa.2018-0197-oa
|View full text |Cite
|
Sign up to set email alerts
|

Real-time Visualization of Breast Carcinoma in Pathology Specimens From Patients Receiving Fluorescent Tumor-Marking Agent Tozuleristide

Abstract: Context.— Resection of breast carcinoma with adequate margins reduces the risk of local recurrence and reoperation. Tozuleristide (BLZ-100) is an investigational peptide-fluorophore agent that may aid in intraoperative tumor detection and margin assessment. In this study, fluorescence imaging was conducted ex vivo on gross breast pathology specimens. Objectives.— To determine the potential of tozuleristide to detect breast ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 25 publications
0
24
0
Order By: Relevance
“…The ability to serially image the cutaneous lesions provided data regarding signal and contrast durability. These data were important in the design of subsequent clinical trials with BLZ-100, which demonstrated efficacy with dosing the day before or day of surgery in CNS [ 11 ] or non-CNS [ 10 ] tumors. A Phase II/III study in pediatric CNS tumors is ongoing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability to serially image the cutaneous lesions provided data regarding signal and contrast durability. These data were important in the design of subsequent clinical trials with BLZ-100, which demonstrated efficacy with dosing the day before or day of surgery in CNS [ 11 ] or non-CNS [ 10 ] tumors. A Phase II/III study in pediatric CNS tumors is ongoing.…”
Section: Discussionmentioning
confidence: 99%
“…BLZ-100 was well-tolerated in definitive toxicology and safety pharmacology studies in rats and non-human primates [ 9 ]. The BLZ-100 Phase 1 clinical development program has included studies in adult glioma (NCT02234297), pediatric CNS tumors (NCT02462629), and breast cancer [ 10 ] and other solid tumors (NCT02496065). The results from Phase I adult glioma have been published in 2020 [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Breast carcinoma : BLZ-100 has also been evaluated in breast cancer for fluorescence-guided pathology ( 50 ). The objective of this study was to investigate the feasibility of using BLZ-100 to (i) target breast carcinoma and (ii) enable demarcation of surgical margins.…”
Section: Blz-100 (Tozuleristide Tumor Paint™; Peptide)mentioning
confidence: 99%
“…The knottin peptide Tozuleristide, which consists of the scorpion venom derived ligand chlorotoxin conjugated to ICG, is currently undergoing clinical translation. This probe was able to distinguish tumor from normal tissue in resected human breast cancer specimens between 1 and 26 h post-injection (Dintzis et al, 2018). Tozuleristide is a naturally occurring knottin, whose exact specificity is not fully known, though MMP-2 and AnnexinA2 have been observed as targets.…”
Section: Molecular-targeted Fluorescent Tracersmentioning
confidence: 99%